2018
DOI: 10.1111/rda.13288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorogenic acid and caffeic acid on the quality of frozen‐thawed boar sperm

Abstract: Chlorogenic acid (CGA) and caffeic acid (CA) are potent antioxidants that are mostly found in coffee beans. This study aimed to investigate the effects of CGA and CA supplementation during semen freezing on the quality of frozen-thawed boar spermatozoa. The antioxidants CGA and CA were added to a semen extender to achieve final concentrations of 50, 100, 200 and 400 µM. Supplementation of 100 µM CGA and CA yielded a significantly higher percentage of sperm viability (increased by 8%-10%) and plasma membrane in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
4
14
1
Order By: Relevance
“…Chlorogenic acids, other active components, exhibited protective effects on sperm plasma [27, 28]. Previous studies have also shown that quercetin, astragalin, kaempferol, feruloylquinic acid, and caffeic acid have beneficial and/or protective effects on improving the reproductive function, preventing sperm damage, ameliorating sperm function, and improving testicular function [2732]. In this study, SPP and WPP showed protective effects on reproductive, endocrine, and testicular function.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Chlorogenic acids, other active components, exhibited protective effects on sperm plasma [27, 28]. Previous studies have also shown that quercetin, astragalin, kaempferol, feruloylquinic acid, and caffeic acid have beneficial and/or protective effects on improving the reproductive function, preventing sperm damage, ameliorating sperm function, and improving testicular function [2732]. In this study, SPP and WPP showed protective effects on reproductive, endocrine, and testicular function.…”
Section: Discussionsupporting
confidence: 55%
“…Total flavonoids, efficacious components of Cuscutae Semen, have been reported to show regulatory effects on reproductive and endocrine function [12, 26], such as regulating LH, T, and E 2 levels. Chlorogenic acids, other active components, exhibited protective effects on sperm plasma [27, 28]. Previous studies have also shown that quercetin, astragalin, kaempferol, feruloylquinic acid, and caffeic acid have beneficial and/or protective effects on improving the reproductive function, preventing sperm damage, ameliorating sperm function, and improving testicular function [2732].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of concentration for the experiments was supported by a recent observation in which the supplementation of 100 μM CGA played a beneficial effect on the quality of frozen-thawed boar spermatozoa [ 30 ]. In addition, our data indicated a positive effect of this concentration on sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…It displays different pharmacological activities such as antioxidant, anti-inflammatory, anti-microbial, hepatoprotective, anticancer, anti-lipidemic, and anti-diabetic [ 29 ]. A concentration of 100 µM CGA yielded beneficial effects on sperm motility, viability, and plasma membrane integrity in boar semen during freezing [ 30 ] and cooling at 15 °C [ 31 , 32 ]. CGA also displayed a positive effect in in vitro production of porcine embryos and a protection against DNA damage induced by OS in oocytes [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that CA limits apoptosis by reducing ROS production and increasing intracellular glutathione levels in HepG2 cells under oxidative stress ( Granado-Serrano et al, 2007 ). Namula et al (2018) suggested that CA supplementation improved certain sperm parameters, including viability, plasma membrane integrity, and motility, during boar sperm freezing. Nguyen et al (2019) found that CA supplementation during in vitro maturation could protect porcine oocytes from DNA damage induced by oxidative stress and improve their subsequent developmental competence after fertilization.…”
Section: Introductionmentioning
confidence: 99%